Structure and spatial consistency of network-based space layouts for building and product design - Suter, Georg (Computer aided design, 2013)
Network-based space layouts are schematic models of whole spaces, subspaces, and related physical elements. They address diverse space modeling needs in building and product design. A schema (data model) for network-based space layouts is defined that is influenced by existing space schemas. Layout elements and selected spatial relations form a geometric network. The network is embedded in 3-space and facilitates analysis with graph and network algorithms. Spatial constraints on layout elements and spatial relations extend the schema to support spatial consistency checking. Spatially consistent layouts are required for reliable network analysis and desirable for layout modification operations. An operation is introduced that evaluates spatial constraints to detect and semi- or fully-automatically resolve spatial inconsistencies in a layout. A layout modeling system prototype that includes proof-of-concept implementations of the layout schema extended by spatial constraints and the inconsistency resolution operation is described. Layouts of a floor of an office building and a rack server cabinet have been modeled with the system prototype. •A schema is defined for space layouts that represent spatial relations as networks.•Spatial constraints for spatial consistency checking extend the schema.•An inconsistency resolution operation resolves inconsistencies in a layout.•A layout modeling system prototype has been implemented and validated with examples.